Perbedaan Tingkat Kematangan Sosial Antara Santri Pondok Pesantren Modern Dan Tradisional - Hilalludin Hilalludin; Ghossan Althof (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Education has a crucial role in shaping the next generation of quality, and in Indonesia, Islamic boarding schools are the oldest Islamic educational institutions that contribute significantly to the development of knowledge and morality. This study aims to analyze the difference in the level of social maturity between modern and traditional Islamic boarding school students, taking into account personal and environmental factors. The research method used is literature research, collecting data from books, journals, and related articles. The findings showed that modern Islamic boarding school students tend to be more individualistic in completing tasks and have wider access to learning facilities, while traditional Islamic boarding school students more often work together and prioritize religious education. Differences in educational environments, teaching methods, and social opportunities contribute to the variety of social maturity of students. Students in both types of boarding schools are expected to have social maturity in accordance with the principles of social maturity. The implication of this study is the importance of understanding the role of the environment and teaching methods in the development of social maturity of students to improve the quality of education in boarding schools.